2021
DOI: 10.3390/molecules26071900
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Graphene from Refined Benzene Extracted from Low-Rank Coal: Based on the CVD Technology

Abstract: Industrial preparation of graphene has been a research hotspot in recent years. Finding an economical and practical carbon source and reducing the cost of production and instrument is significant in industrial graphene production. Coal is a common carbon source. Efficient improvement and utilization in the cleaning of coal has recently been a popular research area. In this study, we developed a set of graphene preparation methods based on Anhui Huainan’s low-rank gas coal (HNGC). Using self-built experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the Raman image (figure 10 a ), it can be observed that the peaks mainly appear at 1346 cm −1 , 1577 cm −1 and 2691 cm −1 , which are the D-band caused by MLG disorder, G-band and the second-order two-dimensional band of MLG, respectively. Therefore, Raman spectroscopy indicated the MLG existing in the wear scar at 600°C [53,54].
Figure 10( a ) Raman spectra ( b–g ) the XPS spectra of wear scar of Ti6Al4V titanium alloy at 600°C.
…”
Section: Resultsmentioning
confidence: 99%
“…In the Raman image (figure 10 a ), it can be observed that the peaks mainly appear at 1346 cm −1 , 1577 cm −1 and 2691 cm −1 , which are the D-band caused by MLG disorder, G-band and the second-order two-dimensional band of MLG, respectively. Therefore, Raman spectroscopy indicated the MLG existing in the wear scar at 600°C [53,54].
Figure 10( a ) Raman spectra ( b–g ) the XPS spectra of wear scar of Ti6Al4V titanium alloy at 600°C.
…”
Section: Resultsmentioning
confidence: 99%
“…Graphene has recently emerged as a promising sensing material owing to its excellent mechanical and electrical properties. , To commercialize graphene, various synthesis protocols have been developed, including mechanical exfoliation, chemical vapor deposition, and chemical reduction of graphene oxide. These methods have the advantage in manufacturing graphene of different grades, and they also present challenges, such as nonscalable production, high energy consumption, and massive waste generation . Laser-induced technology has been recognized as a powerful approach for high-throughput, precisely programmable, and mask-free fabrication of various electronics, such as wearable strain sensors, heterostructure transistors, and flexible electrochemical sensors. , Laser-induced graphene (LIG) on polyimide (PI) substrates has also been explored for patterned strain sensors, achieving controllable physical and electrical properties and tailorable sensitivities , by precisely controlling laser power, speed, and atmosphere. , Herein, we propose a flexible lip-reading strain sensor based on the LIG.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Nobel Prize in Chemistry in 2010 was awarded to the UK for the "groundbreaking experiments regarding the two-dimensional material graphene" [4], opening the knowledge to a broad Research staff with particular interest and needs focused on these materials. It is mentioned pure materials such as Graphene [5], Carbon Nanotubes [6], fullerenes [7,8] as well other Carbon-based allotropes [9] based on Carbon that show unique Opto-electronic [10], conductive [11], and Quantum emissions properties [12]. In this regard, these materials are exposed to those with high performances.…”
Section: Introductionmentioning
confidence: 99%